Toxicity profile and early clinical outcome for advanced head and neck cancer patients treated with simultaneous integrated boost and volumetric modulated arc therapy. Issue 1 (December 2015) - Franzese, Ciro; Fogliata, Antonella; Clerici, Elena; Franceschini, Davide; Villa, Elisa; D'Agostino, Giuseppe; Navarria, Piera; Mancosu, Pietro; Tomatis, Stefano; Cozzi, Luca; Scorsetti, Marta
Abstract Background Shortening the overall treatment time without increasing acute reactions is one of the major aims in radiotherapy for head and neck cancer (HNC). Volumetric modulated arc therapy (VMAT) with Simultaneous Integrated Boost (SIB) showed improvements in outcome and pattern of toxicity. Patients with stage III-IV HNC treated with VMAT-SIB have been analysed, and doses were correlated to limiting structures and toxicity. Methods One hundred two patients treated from December 2008 to August 2014 were analysed. Patients were treated with VMAT (RapidArc) and SIB in 33 fractions for a total dose of 69.96 and 54.45Gy, respectively. For organs at risk, D1/3 V, D1/2 V, D2/3 V, the mean dose, VD withD = 10, 20, 30, 40, 50, 70 Gy were analysed. For targets, D98%, D2%, and V95%, V107%, conformity and homogeneity indexes were calculated. Toxicity was graded according to CTCAE3. Results Oral cavity V30Gy, V40Gy, and V70Gy, were found correlated with mucosal toxicity grading. Concerning salivary glands, significant was only D2/3V for one of the two parotids. Almost all analysed parameters of the inferior constrictor muscle were significant while no correlations were found for middle and superior constrictors. With median follow-up of 19 months, Overall Survival (OS) at 3 and 5 years was 83 % ± 4 % and 73 % ± 10 %. Mean OS was 51 ± 3 months. Disease Free Survival (DFS) at 3 and 5 years was 71 % ± 7 %, and 34 % ± 16 %. Mean DFS was 43 ± 3 months. Conclusions RapidArc technology and SIB with 1.65 and 2.12Gy/fraction for 33 fractions showed a good toxicity profile and encouraging trend for OS and DFS for patients with stage III-IV HNC.